TRAUMATIC BRAIN INJURY, THE GUT MICROBIOME, AND SOCIOECONOMIC STATUS: A REVIEW - Spyropoulos, Daphne Catherine (LIFE: International Journal of Health and Life-Sciences, 2021)
This article reviews existing literature on three bidirectional relationships. These are traumatic brain injury (TBI) and gut microbiome relationship, the TBI and socioeconomic status (SES) relationship, and the gut microbiome and SES relationship. Literature on the relationship between TBIs and the gut microbiome underscores the loop created through the gut-brain axis, leading TBI to disrupt gut microbiota composition and diversity, which in turn aggravate existing neuroinflammation in the brain. Literature on the relationship between TBIs and SES links lower SES to higher occurrence rates of TBI and poorer recovery outcomes. Literature on the relationship between the gut microbiome and SES, links lower SES to gut dysbiosis, presenting as imbalanced gut microbiota composition and lower diversity. The TBI-gut microbiome, TBI-SES, and gut microbiome-SES bidirectional relationships reinforce health inequity and call for social justice advocacy for the protection of brain health of people of lower socioeconomic backgrounds.